(untitled) (Journal of the College of Basic Education, 2022)
The absorption and fluorescence spectra have been studied and measured for Acriflavine (AF) solution which dissolved in [N-N-dimethyl formamide (Dmf) , dimethyl sulphoxide (Dmso) and water] solvents as a function of concentration and solvent at excitation wavelength (λex= 414nm) . Have been calculated peaks the fluorescence spectra of Acriflavine (AF) solution dissolved in N-N-dimethyl formamide (Dmf) and dimethyl sulphoxide (Dmso) at concentration (1x10-5M ) , and found that it is equal to (λmax= 497 ) ، (λmax= 501) and ( λmax= 505), respectively. Also been calculated the value stokes shift of these peaks found to be equal to (1292.5) ، (1316.5) and (2469.7) , respectively. Where we note that (stokes shift) shifted peak of fluorescence spectra towards the longer wavelength (redshift) increases with increase solvent polarity . The increase of solvents polarity lead to decrease in the intensity of the fluorescence spectra . All measurement were at room temperature .